DRIVING IMPULSE BUYING ON TIKTOK SHOP AN S-O-R PERSPECTIVE ON THE ROLE POSITIVE EMOTIONS AS AN MEDIATOR - Ade Kafa Bih; M. Ridwan Basalamah; Mohamad Bastomi (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of Shopping Lifestyle, Flash Sale, and Live Streaming on Impulse Buying with Positive Emotions as a mediating variable among TikTok Shop users in Malang City. Using a quantitative approach, data were collected through online questionnaires from 192 respondents selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. The results of the study show that Shopping Lifestyle and Flash Sale significantly affect Positive Emotions and Impulse Buying. However, Live Streaming was found to have no significant effect on Positive Emotions, although it has a strong direct effect on Impulse Buying. Mediation analysis revealed that Positive Emotions significantly mediate the influence of Shopping Lifestyle and Flash Sale on impulse buying, but do not mediate the effect of Live Streaming. These findings confirm the Stimulus-Organism-Response (S-O-R) theoretical model, in which lifestyle and price promotion stimuli are more effective at eliciting consumers' emotional aspects compared to live broadcast features that tend to be informative. Sellers are advised to package live streaming content in a more entertaining format to appeal to the viewers' emotional side.